Arachidonic acid causes lysis of blood cells and ADP-dependent platelet activation responses in platelet function tests. (17th November 2019) - Ramström, Sofia
Abstract: The use of arachidonic acid (AA) to stimulate platelets is considered as a specific approach to study aspirin treatment efficacy. However, very high concentrations of AA are used, and it has been previously reported that AA can induce cell lysis in other settings. Several clinical studies have reported decreased responses to AA in whole blood tests in the presence of clopidogrel. Our aim was to investigate whether unspecific effects contribute to AA-induced aggregation and platelet activation in light transmission aggregometry (LTA) in platelet-rich plasma (PRP), and in assays using whole blood, multiple electrode aggregometry (MEA, Multiplate®), and flow cytometry. We report that cell lysis, especially of red blood cells, does occur at concentrations of AA used in the clinical tests and that ADP is very important for the AA-induced platelet activation responses. In flow cytometry, very limited platelet activation was detected before reaching AA concentrations in the millimolar range, where cell lysis also occurred, making it problematic to develop a reliable flow cytometry assay using AA as reagent. We conclude that cell lysis and ADP release contribute to AA-induced platelet responses, most markedly in whole blood assays. This finding could potentially explain some differences between studies comparing methods using whole blood and PRP and also how clopidogrel treatment could influence AA-induced aggregation results in previously published studies. Our findings highlight some issues with AA as reagent for platelet activation, which also have an impact on how platelet activation assays using AA should be interpreted.